Comparison of simulated keratometric changes following wavefront-guided and wavefront-optimized myopic laser-assisted in situ keratomileusis - Lee WS (Dove Medical Press, 2018)
Wen-Shin Lee, Edward E MancheDepartment of Ophthalmology, Byers Eye Institute, Stanford University, Palo Alto, CA, USAPurpose: The aim of the study was to determine and compare the relationship between change in simulated keratometry (K) and degree of refractive correction in wavefront-guided (WFG) and wavefront-optimized (WFO) myopic laser-assisted in situ keratomileusis (LASIK).Methods: A total of 51 patients were prospectively randomized to WFG LASIK in one eye and WFO LASIK in the contralateral eye at the Byers Eye Institute, Stanford University. Changes in simulated K and refractive error were determined at 1 year post-operatively. Linear regression was employed to calculate the slope of change in simulated K (ΔK) for change in refractive error (ΔSE). The mean ratio (ΔK/ΔSE) was also calculated.Results: The ratio of ΔK to ΔSE was larger for WFG LASIK compared to WFO LASIK when comparing the slope (ΔK/ΔSE) as determined by linear regression (0.85 vs 0.83, p = 0.04). Upon comparing the mean ratio (ΔK/ΔSE), subgroup analysis revealed that ΔK/ΔSE was larger for WFG LASIK for refractive corrections of >3.00 D and >4.00 D (0.89 vs 0.83; p = 0.0323 and 0.88 vs 0.83; p = 0.0466, respectively). Both linear regression and direct comparison of the mean ratio (ΔK/ΔSE) for refractive corrections <4.00 D and >4.00 D revealed no difference in ΔK/ΔSE between smaller and larger refractive corrections.Conclusion: WFO LASIK requires a smaller amount of corneal flattening compared to WFG LASIK for a given degree of refractive correction. For both, there was no significant difference in change in corneal curvature for a given degree of refractive error between smaller and larger corrections.Keywords: LASIK, keratometry, wavefront guided, wavefront optimized